Praktik Pembagian Waris Anak Angkat Perspektif Hukum Islam, Kompilasi Hukum Islam, Hukum Perdata dan Hukum Adat di Desa Surabayan Kabupaten Lamongan - R. Zainul Mushthofa; Siti Aminah; Dendik Irawan (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
The presence of a child in the household is highly anticipated and expected for all families, but not all families can experience having children so that families must adopt children. In Javanese custom, the adoption of a child is carried out with the aim of being an inducement for families who have not yet been blessed with children, because the Javanese indigenous people believe that by adopting a child as an inducement, the family will later be blessed with their own child. But from the adoption of the child resulted in blood relations and inheritance, whereas in Islamic law this is not the case. The problems in this thesis are, How is the practice of adopting children in Surabayan Village, Sukodadi District, Lamongan Regency, How to determine the number of inheritance rights for adopted children in Surabayan Village, Sukodadi District, Lamongan Regency and what are the views of Islamic Law, Civil Law, and Customary Law regarding inheritance rights of adopted children in Surabayan Village, Sukodadi District, Lamongan Regency. This research is a field research (Field Research), the data sources used are primary data sources collected through interviews, documentation and observation. Primary data is obtained directly from respondents regarding inheritance for adopted children in Islamic law and Javanese customary law, while secondary data is in the form of theories and legal norms as well as other supporting data obtained from literature, documentation and village biographies. All of these data are used to describe a review of Islamic law regarding inheritance for adopted children in the perspective of Javanese customary law.